Ion Transport of Biohybrid Asymmetric Membranes by pH and Light‐Cooperative Modulation - Yujia Lv; Nannan Yang; Shanfu Lu; Yan Xiang (Advanced Materials Interfaces, 2020)
Abstract Bacteriorhodopsin (bR) is an excellent light‐driven proton pump and plays a vital role in chemical and biological analytical processes, such as maintaining osmotic balance, intracellular acidity, and participating in photosynthesis. Inspired by the special membrane structure with 75% bR and 25% lipid forming a purple membrane (PM) embedded on the Halobacterium salinarum cell membrane, an asymmetric membrane is fabricated by covering an anodic aluminum oxide (AAO) with a mixture of PM and poly(vinyl alcohol) (PVA) and ion transport modulation is achieved via coordination of pH and light stimuli. The rectification ratio of the PM‐doped asymmetric membrane is increased from 2 to 14.43 under costimulation of pH and light. Because bR is a conventional proton pump, the mechanism of this device may shed light on the design of other ionic asymmetric membranes (e.g., Na+, Cl−) via homologs of bR.